PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN FIRM SIZE SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA SUBSEKTOR KERAMIK YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Herlina, R R Kezia; Arief, Mohammad Yahya; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Basic Industry and Chemical Companies Sector in the Manufacturing Industry (excluding oil and gas) that produce materials that are processed into finished products. The basic and chemical industry sector has eight subsectors, namely the cement subsector, the ceramics and porcelain subsector, the metal and similar subsector, the chemical subsector, the plastics and packaging subsector, the animal feed subsector, the wood and processing sector, and the pulp and paper sector. The purpose of this study is to examine the influence of Profitability, and Liquidity in influencing the value of companies moderated by Firm Size. This research is an explanatory research. The population in this study is Basic Industry and Chemical companies listed on the Indonesia Stock Exchange 2019-2022. The sampling technique is by purposive sampling. Data analysis and hypothesis testing using the Structural Equation Model – Partial Least Square (PLS-SEM). Results of direct influence hypothesis test using the Smart PLS 3.0 applicationshows that Profitability has a significant positive effect on Value company, Liquidity does not have a significant effect on company value, Firm Size does not have a positive effect on moderating the influence of Profitability on Company Value, Firm Size has a significant negative effect on moderation of the influence of profitability on company value.